Remarks on the Q-tensor model for equilibrium liquid crystal configurations - Ball, J; Majumdar, A (2007)
We study minimizers of the Landau-De Gennes energy functional for liquid crystals in the biaxial and uniaxial cases. We derive the corresponding equilibrium equations and make predictions about the equilibrium order parameters. This, in turn, gives qualitative insight into the structure of the minimizers and can also be used in the numerical analysis of liquid crystal configurations in confined geometries.